Keys to families and genera of gerromorpha and nepomorpha (Insecta: Heteroptera) in the Central Amazonia, Brazil - Pereira, Domingos Leonardo Vieira; Melo, A. L.; Hamada, Neusa (Neotropical Entomology, 2007)
Few studies have been done in Brazil on aquatic and semi-aquatic Gerromorpha and Nepomorpha (Heteroptera), Minas Gerais being the state where these insects have been studied the most. The present study presents keys for identification of Gerromorpha and Nepomorpha adults, thus providing a tool for ecological studies on aquatic insects in Central Amazonia. The specimens used to elaborate the taxonomic keys were collected in Presidente Figueiredo county in streams and artificial lakes and in Manaus county in streams, white-water floodplain (várzea) lakes and Rio Negro blackwater flooded forest (igapó). Specimens from the invertebrate collection of the Instituto Nacional de Pesquisas da Amazonia (INPA) were also examined and included in the keys. Thirty one genera from 13 families of the infra-orders mentioned.
Chaves de identificação para famílias e gêneros de gerromorpha e nepomorpha (Insecta: Heteroptera) na Amazônia Central
Keywords: Animals; Classification; Heteroptera; Histology; Animal; Heteroptera; Gerromorpha; Heteroptera; Hexapoda; Insecta; Invertebrata; Nepomorpha